(untitled) (International Journal of Natural Sciences, 2016)
A descriptive type of cross sectional study on exploring the common oro-dental problems among the patients attending outpatient department of Ohud Dental Care and implant center, Bogra was conducted during the period from May to July 2013. The objectives of this study were to identify the common oro-dental problems for assessing the level of knowledge regarding dental care practices among the respondents. A questionnaire based data were collected and the sample compares 414 respondents of all age groups. The highest percentage of the patients had complaints of periodontitis (73.9%) followed by gingivitis (64.3%), dental caries (40.6%), attrition (10.4%), mobility (5.8%), broken teeth (5.6%) and alveolar abscess (6.3%). Considering the pattern of inflammation, 425.5% had inflammatory or-dental problems and 56.6% had non-inflammatory oro-dental problems. On examination also revealed that 3 1.9% unhealthy gums, 3.9% had unhealthy tonsils, 10.3% had diseased tongue, 10.7% had diseases mucosa and 4.1% had apthus ulcer. The proportion of illiterate patients were higher among the inflammatory disease (16.7%) compared to non-inflammatory disease (9.8%), where as respondents having graduate level of education were higher among the non- inflammatory disease (30.8%) compared to inflammatory diseases (8.3%). There was significant association between the oro-dental problems and food habit (p>O.O5) except liking of sweet and habit of area nut and lime (p<O.05). This indicated that the proportion of non-inflammatory dental problems were higher among the patients habituate with sweet (82.5%) compared to inflammatory disease (72.2%). But the proportion of inflammatory disease was higher among the patients having habituated with chewing areca nut line (35.0%) than non- inflammatory disease (26.1%). Knowledge of causes of dental problems higher among the patients having non-inflammatory disease (62.0%) compared to inflammatory disease (46.7%) and the difference was statistically significant (p<O.001). Similarly, the proportion of visiting dental surgeon was significantly (p<0.001) higher among the patients having non-inflammatory disease (4.4%). International Journal of Natural Sciences (2015), 5(1) 15-20